Effect of Adipic Acid as Crosslinking Agent in Nanocellulose Reinforced Chitosan Biocomposites - Chelsea Chin Sze Yii (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To analyse the properties of nanocellulose isolated from rice straw in terms of the functional group and crystallinity. To evaluate the effect of nanocellulose content on the physical, mechanical and thermal properties of nanocellulose reinforced chitosan biocomposites. To compare the effect of adipic acid on the physical, mechanical and thermal properties of crosslinked and non-crosslinked nanocellulose reinforced chitosan biocomposites.